Performance Evaluation of Pasaman Communication Office in Implementing SPBE and Public Services - Marliani, Marliani (International Journal of Social and Political Sciences, 2025)
This study evaluates the performance of the Pasaman Regency Communication and Information Office (Diskominfo) in implementing the Electronic-Based Government System (SPBE) and delivering public services, as mandated by national digital transformation agendas. In recent years, the Indonesian government has emphasized digital governance as a pathway to enhance transparency, accountability, and efficiency in public administration. Within this context, regional governments are expected to meet SPBE indicators as documented in annual performance reports such as LAKIP. The primary objective of this research is to assess how effectively Diskominfo Pasaman has implemented SPBE, identify enabling and inhibiting factors, and provide recommendations to strengthen regional digital governance. Utilizing a qualitative descriptive method with a case study design, the research draws on document analysis of the 2023 LAKIP report, supported by related regulations and strategic planning documents. The analysis reveals significant progress, with SPBE implementation rising from 20% in 2022 to 50% in 2023, supported by consistent BB predicate ratings in SAKIP assessments and overachievement in program realization (102.12%). However, the study also identifies critical constraints, including limited ICT human resources, regulatory delays, and infrastructure disparities in remote areas. The findings suggest that while numerical indicators show advancement, structural and strategic reforms are needed for sustainable digital transformation. This research concludes that regional SPBE success depends not only on technological tools but also on institutional readiness, legal frameworks, and inclusive access—highlighting the importance of holistic governance in Indonesia’s digital reform efforts.